2019
DOI: 10.1002/srin.201900331
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Microstructure and Corrosion Behavior in Dual‐Phase Steels with Various Si Content

Abstract: The objective herein is to evaluate the effect of silicon on the corrosion behavior of dual‐phase steels. For this purpose, five different steels with various Si content ranging from 0.34 to 2.26 wt% are intercritically annealed at 780 °C for 15 min. It is clarified that the mechanism of the effect of Si on the corrosion behavior of dual‐phase steels is a mutual mechanism. The increase in Si content (from 0.34% to 0.91%) initially reduces corrosion resistance due to a decrease in the volume fraction of martens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It has been confirmed that the silicon element can decrease and increase FGS [28,49]. Nouri et al [49,50] expressed that increasing the silicon content increased FGS. This more likely resulted from decreasing MVF (this reason will be discussed) and increasing the mobility of ferrite grain boundaries [49,50].…”
Section: Fgs Contribution On the Strengtheningmentioning
confidence: 94%
See 4 more Smart Citations
“…It has been confirmed that the silicon element can decrease and increase FGS [28,49]. Nouri et al [49,50] expressed that increasing the silicon content increased FGS. This more likely resulted from decreasing MVF (this reason will be discussed) and increasing the mobility of ferrite grain boundaries [49,50].…”
Section: Fgs Contribution On the Strengtheningmentioning
confidence: 94%
“…Increasing the silicon content decreases the carbon content of the eutectoid point [13]. Consequently, in a constant intercritical annealing temperature and time, the formed volume fraction of austenite, i.e., MVF, is reduced by increasing the silicon content [13,49,50]. M S is enhanced by an aluminum addition.…”
Section: Mvf Contribution On the Strengtheningmentioning
confidence: 99%
See 3 more Smart Citations